2011
DOI: 10.3141/2205-20
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Springtime Low-Volume Road Damage to a Minimum

Abstract: Maintenance of existing road network infrastructure and expansion of networks with new facilities are two major investment categories in the transportation system. Road maintenance projects optimize the scheduling of maintenance activities so that pavement is in good condition and so that road expansion projects add extra capacity to a road network to improve mobility. The two problems are usually considered separately in practice; however, an integrated approach to these two problems was proposed. The road ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Through pavement deflection testing, Hein and Cole (2002) found that the duration of pavement structure weakness can be double that of the time required to achieve complete pavement structure thawing. Kestler et al (2011) recommend that SLRs can be removed when LWD moduli recover to about 80 to 90% of the non-thaw-weakened moduli. Their site studies indicate that sufficient modulus recovery and dissipation of excess moisture occurs about 5 weeks after placement of SLRs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Through pavement deflection testing, Hein and Cole (2002) found that the duration of pavement structure weakness can be double that of the time required to achieve complete pavement structure thawing. Kestler et al (2011) recommend that SLRs can be removed when LWD moduli recover to about 80 to 90% of the non-thaw-weakened moduli. Their site studies indicate that sufficient modulus recovery and dissipation of excess moisture occurs about 5 weeks after placement of SLRs.…”
Section: Introductionmentioning
confidence: 98%
“…Baïz et al (2008), Doré andZubeck (2009), andChapin (2010) provide overviews of the current status of SLR implementation practices in northern jurisdictions. Kestler et al (2011) provide an overview of current diagnostic techniques used to implement SLRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation